Case report: Disseminated histoplasmosis in a renal transplant recipient from a non-endemic region - Chang, Brian; Saleh, Tawny; Wales, Cameron; Kuklinski, Lawrence; Malla, Prerana; Yang, Shangxin; Fuller, David; Nielsen-Saines, Karin (Frontiers in Pediatrics, 2022)
Histoplasmosis is the most common endemic fungal infection in the U.S. The majority of cases are asymptomatic and have clear exposure to endemic regions. In contrast, we present an adolescent immunocompromised patient with systemic and relatively non-specific symptoms including abdominal pain, weight loss, lower extremity edema, and scabbing skin lesions, without known exposure to endemic areas for histoplasmosis. Histologic analysis of gastrointestinal and skin biopsies eventually revealed a diagnosis of disseminated histoplasmosis; patient was successfully treated with amphotericin B followed by itraconazole maintenance therapy. Ultimately, a high bar of suspicion for fungal disease must be maintained in immunosuppressed individuals even without apparent exposure history to endemic areas. This case report serves as a valuable reference for practitioners evaluating differential diagnosis of infections in immunocompromised patients.